2000
DOI: 10.1159/000018840
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative ERCP Approach to Common Bile Duct Stones:Results of a Selective Policy

Abstract: Background: In a previous study, we made a plea for more selective indications for preoperative ERCP in patients with gallstones based on the results obtained from a liberal policy. Following 3.5 years of implementing this selective policy, a report on the results are presented here. This study was performed in a referral academic hospital. Methods: Between June 1994 and December 1997, 328 patients underwent cholecystectomy because of symptomatic cholelithiasis. Absolute indications for preoperative ERCP were:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
9
0
3
Order By: Relevance
“…Although preoperative studies, such as LFTs and ultrasound findings, and clinical data, such as recent pancreatitis, cholangitis, or obstructive jaundice, are not particularly reliable, several studies have supported the practice of selective preoperative ERCP based on the above factors followed by laparoscopic cholecystectomy [8][9][10][11][12][13]33]. It has been suggested by some, in an attempt to limit the number of negative ERCPs before laparoscopy, that preoperative ERCP should be reserved for patients who have documented choledocholithiasis, acute cholangitis, or severe biliary pancreatitis [3,14,18,33]. When IOC demonstrates choledocholithiasis, the choices include: (1) proceed to postoperative ERCP, (2) single-stage laparoscopic procedure with cholecystectomy and laparoscopic bile duct exploration [15,16], or, occasionally, (3) open bile duct exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Although preoperative studies, such as LFTs and ultrasound findings, and clinical data, such as recent pancreatitis, cholangitis, or obstructive jaundice, are not particularly reliable, several studies have supported the practice of selective preoperative ERCP based on the above factors followed by laparoscopic cholecystectomy [8][9][10][11][12][13]33]. It has been suggested by some, in an attempt to limit the number of negative ERCPs before laparoscopy, that preoperative ERCP should be reserved for patients who have documented choledocholithiasis, acute cholangitis, or severe biliary pancreatitis [3,14,18,33]. When IOC demonstrates choledocholithiasis, the choices include: (1) proceed to postoperative ERCP, (2) single-stage laparoscopic procedure with cholecystectomy and laparoscopic bile duct exploration [15,16], or, occasionally, (3) open bile duct exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Using ERCP as a diagnostic procedure to exclude CBD stones in patients undergoing laparoscopic cholecystectomy can lead to performing an ERCP in up to 30% of the patients with sometimes over 50% negative findings, but with associated morbidity. A selective policy can lead to a significant reduction in the number of ERCPs performed and a better yield of stones [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of algorithms using combinations of one-and two-stage surgical and endoscopic approaches that likely morbidity and mortality. [1][2][3][4][5][6][7][8][9][10][11] Others advocate endoscopicbased therapy as a means of decreasing immediate morbidity and mortality particularly in patients who are high-risk surgical candidates, who are in a center with skilled endoscopists, and in whom there is a high suspicion of CBDS. [12][13][14] Recently, a meta-analysis of 12 studies revealed that outcome-defined as successful duct clearance, mortality, overall morbidity, and need for additional procedures-was not significantly different between surgery-only and endoscopy-plus-surgery-treated groups.…”
Section: Introductionmentioning
confidence: 99%